Indonesia 2023 ASEAN’s Chairmanship: Stag Hunt Game Analysis for Indonesia’s Behavior in Facing Myanmar’s Conflict - Muhammad Fachrie (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2026)
This research explains what is the rational choice for Indonesia in facing Myanmar’s Conflict in context of Indonesia 2023 ASEAN’s chairmanship. The conflict in Myanmar is a complex and multifaceted issue, involving various ethnic groups, political actors, and external influences. The conflict is rooted in historical, political, and socio-economic grievances, with deep-seated ethnic and religious divisions exacerbating tensions. The military coup in February 2021 has further escalated the conflict, leading to widespread protests, violence, and human rights abuses. The international community, including ASEAN and other regional powers, have attempted to mediate and facilitate a resolution to the crisis, but progress has been slow and difficult. The situation in Myanmar remains a challenge, with a significant impact on regional and global stability. This research uses the qualitative method by collecting and analyzing secondary data published by institution, organization and other sources. Rational choice and Stag Hunt Game Theory are used to analyze the complexity of Myanmar’s conflict. Eventually, this research found that the rational choice of Indonesia in facing Myanmar’s conflict on its chairmanship is lonely movement in bilateral, regional and international, though there is a hope for strong and concrete cooperation with partners in implementing Five-Point Consensus, UN Resolution and other measures.